Sub-Convulsing Dose Administration of Pilocarpine Reduces Glycemia, Increases Anxiety-Like Behavior and Decelerates Cortical Spreading Depression in Rats Suckled on Various Litter Sizes - Francisco, Elian da Silva; Guedes, Rubem Carlos Araújo (Frontiers in Neuroscience, 2018)
Epilepsy and malnutrition constitute two worldwide health problems affecting behavior and brain function. The cholinergic agonist pilocarpine (300 to 380 mg/kg; single administration) reproduces the human type of temporal lobe epilepsy in rats. Pilocarpine-induced epilepsy in rodents has been associated with glycemia, learning and memory and anxiety disturbances. Cortical spreading depression (CSD) is a neural response that has been linked to brain excitability disorders and its diseases, and has been shown to be antagonized by acute pilocarpine. This study aimed to further investigate the effect of chronic pilocarpine at a sub-convulsing dose on weight gain, blood glucose levels, anxiety-like behavior and CSD. In addition, we tested whether unfavorable lactation-induced malnutrition could modulate the pilocarpine effects. Wistar rats were suckled under normal size and large size litters (litters with 9 and 15 pups; groups L9 and L15, respectively,). From postnatal days (PND) 35–55, these young animals received a daily intraperitoneal injection of pilocarpine (45 mg/kg/day), or vehicle (saline), or no treatment (naïve). On PND58, the animals were behaviorally tested in an open field apparatus. This was immediately followed by 6 hours fasting and blood glucose measurement. At PND60–65, CSD was recorded, and its parameters (velocity of propagation, amplitude, and duration) were calculated. Compared to the control groups, pilocarpine-treated animals presented with reduced weight gain and lower glycemia, increased anxiety-like behavior and decelerated CSD propagation. CSD velocity was higher (p < 0.001) in the L15 groups in comparison to the corresponding groups in the L9 condition. The results demonstrate an influence of chronic (21-day) administration of a sub-convulsing, very low dose (45 mg/kg) of pilocarpine on CSD propagation, anxiety-like behavior, glycemia and body weight. Furthermore, data reinforce the hypothesis of a relationship between CSD and brain excitability. The lactation condition seems to differentially modulate these effects.